2014
DOI: 10.4081/or.2014.5325
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of diaphyseal forearm fractures in children

Abstract: Both bone forearm fractures are common orthopedic injuries. Optimal treatment is dictated not only by fracture characteristics but also patient age. In the pediatric population, acceptable alignment can tolerate greater fracture displacement due to the bone’s ability to remodel with remaining growth. Generally, these fractures can be successfully managed with closed reduction and casting, however operative fixation may also be required. The optimal method of fixation has not been clearly established. Currently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
59
1
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(66 citation statements)
references
References 41 publications
2
59
1
4
Order By: Relevance
“…Finnish [23], American [15], and Japanese [11] studies reported an increasing incidence of pediatric forearm fractures. Whereas in our study, the presentation of this fracture appeared more frequently at an early age; the typical age distribution of these fractures is bimodal; the peak incidence occurs between ages 10-14 years, coinciding with the adolescent growth spurt, with a second smaller peak incidence between 5 and 9 years of age [40]. The reasons for an increase in pediatric radius/ulna fractures remain unclear and require further investigation; it might be related to deficient bone health.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Finnish [23], American [15], and Japanese [11] studies reported an increasing incidence of pediatric forearm fractures. Whereas in our study, the presentation of this fracture appeared more frequently at an early age; the typical age distribution of these fractures is bimodal; the peak incidence occurs between ages 10-14 years, coinciding with the adolescent growth spurt, with a second smaller peak incidence between 5 and 9 years of age [40]. The reasons for an increase in pediatric radius/ulna fractures remain unclear and require further investigation; it might be related to deficient bone health.…”
Section: Discussioncontrasting
confidence: 54%
“…The reasons for an increase in pediatric radius/ulna fractures remain unclear and require further investigation; it might be related to deficient bone health. Recent studies have suggested that the increased fracture risk in otherwise well children may be a function of lower bone mineralization associated with environmental factors, including physical inactivity, poor nutrition, and specific risk factors for vitamin D deficiency, such as limited sun exposure [40]. In fact, in accordance with this hypothesis, another study underlined that most of the forearm fractures were caused by minor trauma [31].…”
Section: Discussionmentioning
confidence: 97%
“…The majority of these fractures are successfully treated non-operatively by manipulative reduction and cast immobilization (Vopat et al. 2014, Sinikumpu and Serlo 2015). …”
mentioning
confidence: 99%
“…[1] We follow this as a guideline and apply cast to children below six years of age and provide plating for those above 14 years.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of forearm fractures is one in 100 and this is more common in six to 14 years of age. [1] In children, 30% of fractures occur in upper limb and among them forearm fractures accounts for 3.4% of all fractures. Among the forearm fractures, about 18% occur in the middle third.…”
Section: Introductionmentioning
confidence: 99%